Stile acuto w chorwackiej poezji barokowej - Fališevac, Dunja (Array, 2000)
Stile acuto in the Croatian baroque poetry The paper presents the phenomenon of the wide reach of stile acuto in the Croatian poetry of the Baroque. The autor shows many examples of its popularity in the works of poets from the region of Dubrovnik and Dalmatia: Ivan Gundulić, Dživo Bunić and Ignjat Đurđević. In the opinion of the autor the assimilation of stile acuto is a sign of a great literary culture of the Croatian readers of that time, who were sufficiently literary concsious and had the sufficient knowledge of the earlier literary fashions to be able to understand the ludic character of literary concepts. The authoress shows as well that stile acuto for the first time in the Croatian literary tradition created the formalistic type of the literary culture corresponding better with the artistic past than with the reality.